The language loss of the indigenous - Devy, G. N. 1950-; Davis, Geoffrey V. 1943-; Chakravarty, Kalyan Kumar 1947- (Routledge, 2017)
This volume traces the theme of the loss of language and culture in numerous post-colonial contexts. It establishes that the aphasia imposed on the indigenous is but a visible symptom of a deeper malaise - the mismatch between the symbiotic relation nurtured by the indigenous with their environment and the idea of development put before them as their future. The essays here show how the cultures and the imaginative expressions of indigenous communities all over the world are undergoing a phase of rapid depletion. They unravel the indifference of market forces to diversity and that of the states, unwilling to protect and safeguard these marginalized communities. This book will be useful to scholars and researchers of cultural and literary studies, linguistics, sociology and social anthropology, as well as tribal and indigenous studies.